Detection of passerines’ loop migration pattern using wing length measurements - Jónás, Bianka; Harnos, Andrea; Csörgő, Tibor (Acta Zoologica Academiae Scientiarum Hungaricae, 2018)
Bird species following a loop migration strategy use different routes during autumn than in the spring season. Birds nesting at different latitudes have different wing morphology. Finding significant differences in the average wing lengths of the same species between the autumn and spring seasons in the same area suggests loop migration. If these differences are also different by sex, this suggests that males and females do not use the same migratory routes. In this study, we analysed wing morphological differences of seven common long-distance migrant passerine species ringed at the Ócsa Bird Ringing Station from 1984 to 2014. Species were divided into three groups based on moult strategies (pre-, postnuptial and double moult). Based on differences in wing length distributions and means between autumn and spring, six of the seven passerine species follow loop migration. While wing length differences can be adequate to detect loop migration, the species specific moult strategies, the nesting sites and distribution ranges need to be known.